Vertically aligned hierarchical nano-architectures for highly efficient and stable solution processable solar cells - Irfan, Ahmed (2017)
Intense research in the field of nanostructured solar cells (NSCs) brought them to a level of delivering photoconversion efficiency (PCE) ~ 14.3% and 20.2% (η) for dye sensitized solar cells (DSCs) and perovskite solar cells (PSCs), respectively. The state-of-the-art DSCs and PSCs typically employ a thin film of mesoporous TiO2 nanoparticles (NPs) as an electron transport layer (ETL) due to its high specific surface area (~150 m2/g). Despite the high efficiency achieved in both devices using TiO2NPs, there have been significant concerns regarding their inferior electronic mobility (1×10-7 cm2V-1s-1) that results in the loss of photogenerated electrons via recombination, inferior light harvesting properties and instability when exposed to UV-light. For a successful practical deployment of NSCs it is therefore crucial to overcome these intrinsic limitations by introducing suitable alternative morphologies. Towards this end, a vertically aligned TiO2 nanorod provides two orders of magnitude higher electron mobility than their NPs analogues and therefore often demonstrates efficient charge collection in NSCs. However, due to their lower surface area, the performance of DSC and PSCs using pristine TiO2 NRs has been far lower than NPs based analogues, ~3% and ~9.4%, respectively. This thesis describe synthesis of vertically aligned TiO2 NRs via a hydrothermal process on conducting glass substrates (FTO) and their usefulness as an ETL in DSCs and PSCs and also in perovskite solar modules (PSMs). The pristine TiO2 NRs based DSCs resulted in PCE (~1.37%) which is far lower than the best performing DSCs due to the lower surface area. To overcome the low performance, layered NR architectures were introduced that employ TiO2 NPs multi-layers over interface engineered NRs, resulting in a remarkable PCE (~11.2%) in the best performing device. The photovoltaic (PV) parameters of the layered NR DSC, i.e., short circuit density (Jsc ~21.2 mA cm–2), open circuit voltage (Voc ~764 mV) were far higher than a NP reference DSCs, i.e., 11.42 mA cm–2, 720 mV and PCE ~5.1%. The observed high PCE in layered photoanodes is due to their two times higher dye loading, improved light scattering and high surface area than the pristine analogues. The NRs werefurther investigated as a photoanode in PSCs resulting in PCE~ 6.4% in pristine form, where a low PCE is attributed to poor surface roughness of the NRs that result in a weaker interaction with perovskite crystals. A post-treatment of TiO2 NRs is carried out which doubled the PV performance of PSCs resulting in PCE as high as ~ 12.2%, primarily due to efficient charge separation at ETL/Perovskite interface. In addition, the NRs based PSCs also showed durable PV performance compared to NPs counterparts when tested for a shelf-life of 60 days. Perovskite solar module (PSM, best and av. PCE 10.5% and 8.1%), which employs TiO2 NRs as electron transport layer, that showed an increase in performance (~5%) even after shelf life investigation for 2500 h. Investigation shows that the active layer of perovskite (CH3NH3PbI3-xClx) shows superior phase stability when incorporated in devices with TiO2 NRs scaffold as compared their NPs counterpart.The results of this research provide directions to not only achieve high efficiency in NSCs but also, more importantly, to attain long term stability in these devices eventually paving ways for their commercial deployment.